Prangos aricakensis (Apiaceae), a new species from eastern Turkey - Behçet Lütfi̇; Yapar, Yakup; Olgun, Şükrü (Phytotaxa, 2019)
Prangos aricakensis is described and illustrated as a new species from eastern Anatolia (Turkey), where it is known from a single locality in Arıcak (Elazığ) district. Its diagnostic characters are discussed and taxonomic comments are presented. Prangos aricakensis is similar to P. turcica, P. hulusii, P. ilanae and P. trifida, but it differs in hair, leaf, bract, bracteole and fruit characteristics. Fruit and pollen characteristics were investigated using ligth (LM) and scanning electron microscopy (SEM). Data on ecology and IUCN conservation status are also shown.